Prevalence of mental disorders and their associations with age at diagnosis and time since diagnosis of nasopharyngeal cancer - Wang, Wen-Xuan; Wu, Yi-Shan; Qi, Li-Ping; Wu, Anise M. S.; Zhu, Ying-Ying; Gong, Wei-Jie; Guo, Shan-Shan; Hua, Yi-Jun; Luo, Dong-Hua; Chen, Qiu-Yan; Xiang, Yan-Qun; Zhang, Jin-Xin; et al. (Frontiers in Public Health, 2024)
BackgroundDespite advancements in cancer treatment, understanding the long-term mental health implications for nasopharyngeal carcinoma (NPC) survivors remains an underexplored area. This study aims to examine the prevalence of mental disorders and their correlations with age at diagnosis and time since diagnosis among NPC survivors.MethodsA total of 1872 NPC patients were surveyed from September 2020 to June 2021 in this cross-sectional survey. Logistic regression models were used to analyze the associations of age at diagnosis and time since NPC diagnosis with the risk of mental disorders. Additionally, the potential nonlinear trend between these factors was examined using restricted cubic splines. Analyses were conducted both overall and stratified by gender. Gender interaction was also examined.ResultsThe prevalences of depression, anxiety, and sleep disorders were 32.4, 33.2, and 61.5%, respectively. Age at NPC diagnosis was significantly associated with an elevated risk of depression (adjusted OR (aOR): 1.75 for 30–39 years old; 2.33 for 50–59 years old; 2.59 for ≥60 years old) and sleep disorders (aOR: 2.41 for 40–49 years old; 1.95 for 50–59 years old; 2.26, for ≥60 years old), compared to patients diagnosed with NPC at age < 30 years. Conversely, the risk of depression, anxiety, and sleep disorders exhibited negative associations with the time since diagnosis, compared to patients <3 months. Notably, significant nonlinear associations were observed between time since diagnosis and the risk of depression, anxiety, and sleep disorders, which showed an initial increase, with the highest risk occurring at approximately 3.0 (ORmax: 2.7), 1.5 (ORmax: 2.1), and 4.0 (ORmax: 1.9) months since NPC diagnosis, followed by a gradual recovery to a lower risk level at around 12 months. No gender interactions were observed.ConclusionThe prevalence of mental disorders is notable among NPC survivors, showing a positive correlation with age at diagnosis while displaying a negative correlation with time since diagnosis, thus indicating the need for psychological support, especially within the initial several months following NPC diagnosis.